2014
DOI: 10.1103/physrevb.89.155410
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of ferroelectricity and single electron tunneling

Abstract: We investigate the interplay of ferroelectricity and quantum electron transport at the nanoscale in the regime of Coulomb blockade. Ferroelectric polarization in this case is no longer the external parameter but should be self-consistently calculated along with electron hopping probabilities leading to new physical transport phenomena studying in this paper. These phenomena appear mostly due to effective screening of a grain electric field by ferroelectric environment rather than due to polarization dependent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…From the first glance physics of such ferroelectric should be similar to physics of SET considered in Ref. 15 with ferroelectric source and drain capacitors. But this is not so.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…From the first glance physics of such ferroelectric should be similar to physics of SET considered in Ref. 15 with ferroelectric source and drain capacitors. But this is not so.…”
Section: Introductionmentioning
confidence: 68%
“…Recently it was shown that the presence of ferroelectricity in the source and drain tunnel junctions of single electron transistor (SET) induces memory effect in the current-voltage characteristics even in the limit of negligible hysteresis of the ferroelectric insulators. 15 The bottle-neck of ferroelectric SET is the experimental difficulty to produce ultrathin and ultra small ferroelectric tunnel junctions with special parameters. Technologically it is much easier to produce a nanothin ferroelectric layer but not thin enough for perfect electron tunneling.…”
Section: Introductionmentioning
confidence: 99%
“…Following the mean field theory of the SET with "slow" and weak dielectric layer (0 < χ 0 < χ cr 0 ) [24] in the gate capacitor the conductance in the vicinity of Q 0 = e/(2ǫ 0 ) has the form…”
Section: Tfe < Tcmentioning
confidence: 99%
“…Nanomechanical resonators are usually studied as linear oscillators. In contrast, the FE layer shows the non-linear response since the electric fields in the SET capacitors can exceed the FE saturation field [23,24]. Another important difference is related to the fact that the characteristic time scales of FE materials can be essentially lower than those of the nanomechanical systems and can be even comparable with characteristic times of SET.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation